Experiential learning workshops on a group of student-teachers’ intercultural awareness, as the first component of ICC - Sierra Ramírez, Mariana Alejandra; Ballén Jiménez, Jessica Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (125 páginas) : figuras, tablas.